Low Prevalence of Hepatitis B Infections Among Residents of an Institution for the Mentally Retarded in New Mexico - Mann, Jonathan M. (1984)
Residential institutions for the mentally retarded are considered high-risk settings for hepatitis B (HB) infection. Accordingly, HB vaccine is recommended for susceptible clients and selected staff of such facilities. However, a serologic screening program among 364 residents of Los Lunas Hospital and Training School (LLHTS) in New Mexico found only 11 residents to be anti-HBc positive (3%) and only one of these residents was also HBsAg-positive (0.3%). The unexpectedly low prevalence of HB infections at LLHTS probably reflects infrequent HB introductions into the institution. Using these serologic data, a vaccination program was instituted to prevent HB infection among LLHTS residents, thereby eliminating the need for mass screening and HB vaccination of LLHTS employees. Serologic screening among residents of other smaller institutions for the mentally retarded is recommended before design of HB prevention programs for clients and staff.